Study of Consumer Acceptance on Pempek Freshwater Mussels (Pilsbryoconcha exilis) added with Different Ratio of Durian Seed Flour - Dandi Permai Dani Ginting; Sumarto Sumarto; Dewita Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThis study aimed to determine consumer acceptance on pempek freshwater mussels with the addition of durian seed flour. The research method was experimental with a non-factorial completely randomized design (CRD) with 4 treatment levels, namely E0 (without the addition of durian seeds flour), E1 = 40g (20% durian seed fluor), E2 = 80g ( 40% durian seed flour), E3 = 120 g (60% durian seed flour). The parameters tested were organoleptic values (appearance, taste, texture and aroma) and proximate analysis (moisture content, protein content, ash content and fat content). Based on the parameters tested, the best treatment for pempek freshwater mussels with the addition of durian seed flour was E1 (40 g durian seed flour) with an appearance value of 6.92 (light brownish appearance), aroma 6.70 (durian seed aroma), flavor 7,20 (light felt durian seed) and 7.20 texture (chewy texture) while the proximate analysis was 54.23%, moisture 11.4%, protein 1.20%, fat, and 3.25% ash. Keywords: freshwater mussels, pempek, consumer acceptance, durian seed flour